The Thyroid Stimulating Hormone and Free Thyroxine Levels in Correlation with Serum Bilirubin in Neonatal Jaundice - Elvira Dwijayanti; MI. Diah Pramudianti; Dian Ariningrum (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Congenital hypothyroidism is known to cause prolonged hyperbilirubinemia in neonates. It also correlates with delayed maturation of the activity of the uridine diphosphate glucoronosyltransferase (UDPG-T) enzyme. Thus, this study was performed to analyze the correlation of TSH and FT4 levels with serum bilirubin in neonatal jaundice. This observational analytical study with a cross-sectional approach was conducted on 64 neonatal patients with jaundice in Dr. Moewardi General Hospital, Surakarta during September-November 2019. The data comparison and correlation were analyzed with Mann-Whitney and the Spearman test. A p-value of < 0.05 was considered significant with 95% Confidence Interval (CI). The study variables comprised of total bilirubin of 12.7 (6.28-23.5) mg/dL, direct bilirubin of 0.8 (0.30-6.61) mg/dL, indirect bilirubin of 11.87 (3.16-22.94) mg/dL, TSH of 4.4 (0.40-0.06) uIU/L, and FT4 of 22.85±7.4 pmol/L. The TSH and FT4 were moderately correlated with total bilirubin r=-0.444; p=0.001 and r= -0.467; p=0.001), with indirect bilirubin (r= -0.3362; p=0.03 and r=-0.411; p=0.001) and with direct bilirubin (r= -0.257; p=0.040 and r=0.232; p=0.065), respectively. A moderate correlation of TSH and FT4 with total and indirect bilirubin, as well as a weak correlation between TSH and direct bilirubin were found, while no correlation was found between FT4 and with direct bilirubin. Thyroid function screening is recommended in neonates with jaundice, due to the importance of thyroid hormones in the function and formation of organs.